Utilization of Mangrove Ecosystems on Producing Biotechnology Products: A Mini Review - Sofyana, Neng Tanty; Refli, Redoyan (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2024)
Mangrove forests are the main ecosystem that supports the lives of communities in coastal areas. Mangrove forests have been utilized by humankind for so long. So far, the use of mangrove areas has been more ecological and tourism-oriented. However, the use of mangrove plants, for example fruit and leaves, to be processed into products has not been widely explored for industry. Processing products using biotechnology principles such as functional food, body care, and natural dyes (batik) can be an alternative in the utilization and industrialization of mangroves to increase the income or standard living of people living around the mangrove ecosystem. This article reviews the current conditions regarding the use of mangrove plants in Indonesia and their potential for the industrialization of products made from mangrove plants.